1H-Indole-3-carbaldehyde 2-nitrobenzoyl-hydrazone hemihydrate - Ali, Hapipah Mohd; Ng, S.W.; Halim, A.; Nadiah, S. (International Union of Crystallography, 2005)
In the title structure, C16H12N4O 3·0.5H2O, the uncoordinated water molecule lies on a special position of site symmetry 2; O-H⋯O and N-H⋯O hydrogen bonds link the water and organic molecules into a layer structure. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.